2020
DOI: 10.1116/6.0000190
|View full text |Cite|
|
Sign up to set email alerts
|

Patterning nickel for extreme ultraviolet lithography mask application I. Atomic layer etch processing

Abstract: The stringent requirement for patterning highly absorbing metal thin films as a mask for the next-generation extreme ultra-violet lithography system dictates the development of an atomic layer etching process to tailor the etch rate and the etch profile. A “plasma-thermal” atomic layer etching process is developed where an oxygen plasma is used to convert the metallic Ni layer into NiO, followed by formic acid vapor reacting with NiO to form nickel formate [Ni(COOH)2], thereby removing nickel. The directionali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Subsequently, an exposure to formic acid for 1 h removed the oxidized nickel and produced a Ni etch rate of 6 nm/cycle. 36…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, an exposure to formic acid for 1 h removed the oxidized nickel and produced a Ni etch rate of 6 nm/cycle. 36…”
Section: Introductionmentioning
confidence: 99%
“…The etch rate observed for nickel under the Cl 2 and H 2 plasma conditions was 57 Å/cycle . A hybrid technique involving reactive-ion etching and ALE has also been shown to remove nickel. , The nickel ALE process used oxygen plasma to create an oxidized NiO surface. Subsequently, an exposure to formic acid for 1 h removed the oxidized nickel and produced a Ni etch rate of 6 nm/cycle …”
Section: Introductionmentioning
confidence: 99%
“…Etching study on Cr has been reported [20], and for the etching of Cr, a precise etching control was performed using ion milling or atomic layer etching (ALE), but Cr also has a low extinction coefficient for the next generation EUV absorber. Recently, a research on the etching of Ni, a material with a higher extinction coefficient than Tabased materials, has been investigated through a plasmathermal ALE method, and a precisely control of Ni etching and anisotropic etching by repeating oxidation and a ligand exchange have been reported [21,22]. However, there are no sufficient studies on the etching of EUV materials with high absorption coefficients applicable to the next generation EUV mask such as precise etching characteristics, the evaluation of etch selectivity with the capping layer, the degree of damage to the capping layer during the etch process, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a novel process combining plasma activation and thermal removal was developed and successfully applied to directionally etch Ni 4,5 and Cu. 6 This process is illustrated in with organic etchants that react with the surface oxide to form volatile complexes and water, eliminating the need for an extra energy source and avoiding redeposition.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a novel process combining plasma activation and thermal removal was developed and successfully applied to directionally etch Ni , and Cu . This process is illustrated in Figure .…”
Section: Introductionmentioning
confidence: 99%